Progressive Quranic Interpretation as a Pedagogical Strategy for Promoting Inclusive and Contextual Islamic Thought - Karman; Maslani; Nursaid; Suntiah, Ratu (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
Progressive Qur’anic interpretation as a contextual approach to understanding the Qur’an has been extensively developed at the theoretical level, but its implementation in Islamic higher education remains underexplored. Most institutions in Southeast Asia still adhere to traditional exegetical models that are less responsive to contemporary issues such as gender equality, environmental crises, and religious pluralism. This study aims to fill that gap by exploring the application of progressive interpretation as a pedagogical strategy in the Qur’an and Tafsir Study Program (PSIAT) at the Graduate School of UIN Sunan Gunung Djati Bandung. Using a qualitative case study approach, data were collected through curriculum document analysis, semi-structured interviews, and classroom observations. Thematic analysis was conducted through open, axial, and selective coding, focusing on principles of justice, social relevance, and interdisciplinarity. The findings show that PSIAT systematically integrates progressive interpretation into its curriculum through digital, interdisciplinary, and contextual approaches. Students demonstrated positive responses by developing critical thinking and actively engaging with contemporary social issues. This study offers an empirical contribution to the development of a tafsir curriculum in Islamic higher education that is more inclusive, transformative, and relevant to modern challenges.